Autumn cookie cutters [library of things]
Food-grade 430 Stainless Steel: durable material, no crack, long-lasting. Protective PP Grip: comfort PP grip and smooth cut edge avoids finger hurts, safe for adults, kids to use. Perfect for cutting cookie dough, fondant, biscuit, soft fruits, vegetables, cake, brownies, bread, sandwiches, cheese, salad, pancake, chocolate, craft clay, etc.